Methodology for updating GO-FLOW model to handle scenario changes in nuclear power plants - Xinyu, Dai; Ming, Yang; Jipu, Wang; Zhihui, Xu; Hanguan, Wen (Frontiers in Energy Research, 2023)
The design of a nuclear power plant is proved to be safe enough in various hypothetical operation scenarios after strict safety assessment. One of the important tasks of operational risk management in a nuclear power plant is to evaluate whether any configuration change of the nuclear power plant can still achieve its expected safety and economic goals. This paper proposes a system reliability modeling and analysis method based on two-layers hierarchical GO-FLOW model. By flexibly adjusting the parameters of a GO-FLOW model, the model can adapt to the changes of success criteria and various configuration of the modeled system, thus avoiding the extra workload brought by re modeling and improving the efficiency of risk management in nuclear power plants.